The Feminist Utopia Project : Fifty-Seven Visions of a Wildly Better Future - Kauder-Nalebuff, Rachel; Brodsky, Alexandra (Book collections on Project MUSE., 2015)
What do we want? In this groundbreaking collection, more than fifty cutting-edge voices, including Melissa Harris-Perry, Janet Mock, Sheila Heti, and Mia McKenzie, invite us to imagine a truly feminist world. An abortion provider reinvents birth control, Sheila Bapat envisions an economy that values domestic work, a teenage rock band dreams up a new way to make music, Katherine Cross rewrites the Constitution, and Maya Dusenbery resets the standard for good sex. Combining essays, interviews, poetry, illustrations, and short stories, The Feminist Utopia Project challenges the status quo that accepts inequality and violence as a given and inspires us to demand a radically better future.